Water adsorption characteristics and microcalorimetric studies of MOF-5 and MOF-199 synthesized using green sol-gel - Misran H.; Othman S.Z.; Mahadi N.; Aspanut Z.; Lockman Z.; Matsumoto A.; Amin N. (Polish Academy of Sciences, 2023)
Adsorption isotherms; Air; Alcohols; Crystalline materials; Hydrophilicity; Ion exchange; Metallic compounds; Metals; Morphology; Organometallics; Palm oil; Phase interfaces; Silica; Single crystals; Sol-gel process; Sol-gels; Air water interfaces; Auto-oscillations; Environmental-friendly; Framework structures; Metal oxide precursors; Microcalorimetric study; Octahedral structures; Porous templates; Driers (materials)